The book as object in Ray Galton and Alan Simpson's Hancock Half Hour episode 'The Missing Page'. Issue 2 (2nd July 2016) - Egan, Gabriel
ABSTRACT: In their scripts for the television and radio shows of Hancock's Half Hour, Ray Galton and Alan Simpson formulaically employed prolepsis to enable rapid composition of an ironic twist for each episode's ending. For each denouement, a moment from earlier in the episode was revisited and amplified, sometimes explicitly, but more often because, one senses, the writers sought inspiration by looking over what they had already written to see if a suitable candidate moment could be reworked. By the beginning of the second radio series (April–July 1955), the expectation of an ending that recapitulated an antecedent moment was firmly established, and in the finest episodes, Galton and Simpson show an ironic self-consciousness about formulaic writing and the sense of an ending. The self-consciousness is most apparent in the celebrated television episode called 'The Missing Page'.